High Nature Value Farmland: Assessment of Soil Organic Carbon in Europe - Gardi, Ciro; Visioli, Giovanna; Conti, Federica D.; Scotti, Marco; Menta, Cristina; Bodini, Antonio (Frontiers in Environmental Science, 2016)
High Nature Value Farmland (HNVF) is commonly associated with low intensity agricultural systems. HNVFs cover approximately 32% of the agricultural land in Europe and are of strategic importance for the European Union policy since they are reservoirs of biodiversity and provide several ecosystem services. Carbon sequestration is an important service that can be supplied by HNVFs as addressed in this study. Considering soil carbon content as a proxy for soil carbon storage, we compare HNVFs with soils that undergo more conventional land management (nHNVFs) and study the consequences of diverse land uses and geographic regions as additional explanatory variables. The results of our research show that, at the European level, organic carbon content is higher in HNVF than in nHNVF. However, this difference is strongly affected by the type of land use and the geographic region. Rather than seeing HNVF and nHNVF as two sharply distinct categories, as for carbon storage potential, we provide indications that the interplay between soil type (HNVF or nHNVF), land use and geographic region determines carbon content in soils.